Social determinants of health and preventable emergency department patient encounters among adults with hypertension. Issue 1 (15th November 2022) - Ware, Katilya S.; Chidume, Tiffani; Chou, Chiahung
Abstract: Limited access to resources promoting optimal health outcomes can lead to increased emergency department utilization for conditions often manageable by primary care resulting in rising healthcare costs, overcrowding in emergency departments, and poor patient outcomes. Social determinants of health often affect an individual's ability to achieve optimal health. To examine the association between social determinants of health and hypertension‐related patient encounters among adults, we analyzed data from a 340‐bed community hospital in the southeast region of the United States. Gender, race, and geographic location were strongly associated with hypertension‐related encounters. Hypertension‐related encounters in the emergency department were highest in women, African Americans, and young adults. Insurance status and geographic location were also strongly associated. Public health nursing is positioned to prevent disease and increase access to care, considering hypertension‐related encounters in the emergency department account for a significant number of overall visits.